Design Model of CO2 Injection Monitoring Into Depleted Oil Reservoir Using Induced Seismicity Data - Harith, Z.Z.T. (2008)
In many cases, fluid injection into reservoir becomes an important thing in some process such as exploitation in geothermal field. The fluid injection leads to the increase of pore pressure. This will reduce the strength of the rock and may cause failure occur. Due to this phenomenon, new fracture or reactivation of fault will be produced. Usually, local micro earthquake or swarm will be triggered in this area as induced seismicity. Seismic activity will increase with the increasing flow rate of injection fluid into reservoir. Not only in geothermal field, is fluid injection into reservoir also conducted in oil and gas reservoir and in waste disposal process like CO2 injection. In this paper, induced seismicity was used to simulate CO2 injection monitoring using tomography travel time method. Two hundred of micro earth quake have been generated and recorded using five and ten receiver configurations. All the events were assumed as seismic sources where the seismic wave was propagated from this point to the receivers through medium. Two blocks of positive and negative anomaly were placed at the depth of 2-3 km in the reservoir. Those were reconstructed through tomography method using this configuration. The result showed that image of anomaly at 2 km had good resolution and could be reconstructed finely; anomaly at 2.5-3 km could be reconstructed poorly using five receiver configurations. Using extra receivers, the quality of image in this area could be improved.